The population question in a neoclassical growth model: A brief theory of production per capita - Tim Lüger (Technische Universität Darmstadt, Department of Law and Economics, 2019)
This work seeks to answer the "population question," i.e. the effect of population growth on production per capita. This question has lingered in economic thought for centuries and to this day two general lines of thought can be identified, which might be marked as the "optimist" and the "pessimist" view. While the optimists claim that an increase in population will - chiefly owed to concomitant specialization and technological progress - raise average production per capita, the pessimists maintain that the latter would decline as a result of resources becoming relatively more scarce. Integrating both approaches and using a neoclassical framework, this work intends to show that sustainably increasing productivity is predominantly the result of reducing too high fertility toward a lower level such that diminishing returns are outweighed by the benefits from labor division. The paper argues that the historical reduction of fertility can almost completely explain long-run development.
urn:nbn:de:tuda-tuprints-85708
Keywords: B12; B22; J1; O47; N01; N3; 330; Population Question; Division of Labor; Diminishing Returns; Demographic Transition; Economic Development; Classical Growth Theory; Neoclassical Growth Theory; Unified Growth Theory; History of Economic Thought